2015
DOI: 10.1523/eneuro.0094-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Onset of Motor Deficits in a Mouse Model of Spinocerebellar Ataxia Type 6 Precedes Late Cerebellar Degeneration

Abstract: Spinocerebellar ataxia type 6 (SCA6) is an autosomal-dominant cerebellar ataxia that has been associated with loss of cerebellar Purkinje cells. Disease onset is typically at midlife, although it can vary widely from late teens to old age in SCA6 patients. Our study focused on an SCA6 knock-in mouse model with a hyper-expanded (84X) CAG repeat expansion that displays midlife-onset motor deficits at ∼7 months old, reminiscent of midlife-onset symptoms in SCA6 patients, although a detailed phenotypic analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 37 publications
11
69
0
Order By: Relevance
“…We used SCA6 84Q/84Q mice harboring an expanded polyglutamine (poly-Q) repeat which have been shown to display ataxic symptoms at 7 months old (Watase et al, 2008; Jayabal et al, 2015). We have previously shown that there is no Purkinje cell loss at 7 months when disease symptoms are first observed, although Purkinje cell loss is detectable at 2 years (Jayabal et al, 2015). We first wondered whether disease-related torpedoes would be observed in these mice at 2 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used SCA6 84Q/84Q mice harboring an expanded polyglutamine (poly-Q) repeat which have been shown to display ataxic symptoms at 7 months old (Watase et al, 2008; Jayabal et al, 2015). We have previously shown that there is no Purkinje cell loss at 7 months when disease symptoms are first observed, although Purkinje cell loss is detectable at 2 years (Jayabal et al, 2015). We first wondered whether disease-related torpedoes would be observed in these mice at 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…We found, however, that developmental torpedo density was normal in P11 SCA6 84Q/84Q mice compared to WT, suggesting that they are not directly related to later pathophysiology (P11 WT: 2.71 ± 0.90 torpedoes/section; P11 SCA6 84Q/84Q : 2.61 ± 0.54 torpedoes/section; not significantly different, P = 0.92; Figure 8B , left). We also measured the density of Purkinje cell torpedoes in SCA6 84Q/84Q and litter-matched mice at 7 months, when cerebellar-related motor deficits are observed without detectable Purkinje cell loss (Jayabal et al, 2015, 2016a), and found that torpedo density was low at 7 months and similar in both WT and SCA6 84Q/84Q mice (7 month WT: 0.57 ± 0.20 torpedoes/section; 7 month SCA6 84Q/84Q : 0.42 ± 0.13 torpedoes/section; not significantly different; P = 0.53; Figure 8B , middle). Note that we observe higher torpedo numbers in P11 mice than 7-month-old mice in both WT and SCA6 84Q/84Q mice, which is consistent with our observations of a transient developmental peak of torpedoes at P11 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations